Gut microbiota in cats with inflammatory bowel disease and low-grade intestinal T-cell lymphoma - Drut, Amandine; Mkaouar, Héla; Kriaa, Aicha; Mariaule, Vincent; Akermi, Nizar; Méric, Tristan; Sénécat, Odile; Maguin, Emmanuelle; Hernandez, Juan; Rhimi, Moez (Frontiers in Microbiology, 2024)
In cats and humans, several physiological and environmental factors have been shown to alter the gut microbiota of healthy individuals. Cats share several diseases with humans such as inflammatory bowel diseases and low-grade intestinal T-cell lymphoma. The physiopathology of these chronic enteropathies is poorly understood but may involve disequilibrium of the gut microbiota composition and disruption of normal microbiome activity profiles. These disorders are increasingly diagnosed in the feline species due to improved medicalization and easier access to endoscopy in veterinary practice. This review addresses the current data on the gut microbiota of cats in health and in chronic enteropathies. Such functional analysis will help the advancement of innovative diagnostic tools and targeted therapeutic strategies.